Model Integer Linear Programming pada Optimisasi Distribusi Logistik di Daerah Bencana - Kasim, Miranti H.; Djakaria, Ismail; Yahya, Lailany (Research in the Mathematical and Natural Sciences, 2022)
Logistics distribution in disaster-affected areas includes the delivery of relief goods (food, medicine, and clothing) using three types of vehicles with different carrying capacities for each vehicle. In distributing relief goods, unfulfilled requests can occur in disaster-affected areas. This problem can be modeled in the form of integer linear programming because there is a variable that must be an integer value to minimize unfulfilled demand for all types of relief goods at each point of demand. The branch and bound method can solve this problem's integer linear programming model. The next model is simulated using the LINGO 11.0 programming language. The simulation results show that the system can be considered feasible to use. Thus, the vehicle allocation is also obtained in each period with distribution costs from the point of supply to the point of demand. This distribution process lasts for four periods by showing a change in the number of unfulfilled requests. In the last period, there was no more unfulfilled demand for aid to obtain optimal results.